Coagulation disorders in patients with severe hemophagocytic lymphohistiocytosis. - Sandrine Valade; Bérangère S Joly; Agnès Veyradier; Jehane Fadlallah; Lara Zafrani; Virginie Lemiale; Amélie Launois; Alain Stepanian; Lionel Galicier; Claire Fieschi; Adrien Mirouse; Jean Jacques Tudesq; et al. (PLoS ONE, 2021)
Background Coagulation disorders are common in patients with hemophagocytic lymphohistiocytosis (HLH), associated with an increased risk of bleeding and death. We aim to investigate coagulation disorders and their outcome implications in critically ill patients with HLH. Methods We prospectively evaluated 47 critically ill patients with HLH (median age of 54 years [42-67]) between April 2015 and December 2018. Coagulation assessments were performed at day 1. Abnormal standard coagulation was defined as prothrombin time (PT) <50% and/or fibrinogen <2g/L. HLH aetiology was mostly ascribed to haematological malignancies (74% of patients). Results Coagulation disorders and severe bleeding events were frequent, occurring in 30 (64%) and 11 (23%) patients respectively. At day 1, median fibrinogen level was 2∙65g/L [1.61-5.66]. Fibrinolytic activity was high as suggested by increased median levels of D-dimers, fibrin monomers, PAI-1 (plasminogen activator inhibitor) and tPA (tissue plasminogen activator). Forty-one (91%) patients had a decreased ADAMTS13 activity (A Disintegrin-like And Metalloproteinase with ThromboSpondin type 1 repeats, member 13). By multivariable analysis, the occurrence of a severe bleeding (OR 3.215 [1.194-8.653], p = 0∙021) and SOFA score (Sepsis-Related Organ Failure Assessment) at day 1 (OR 1.305 per point [1.146-1.485], p<0∙001) were independently associated with hospital mortality. No early biological marker was associated with severe bleeding. Conclusions Hyperfibrinolysis may be the primary mechanism responsible for hypofibrinogenemia and may also participate in ADAMTS13 degradation. Targeting the plasmin system appears as a promising approach in severe HLH-related coagulation disorders.